Supervised Versus Home Exercise Training Programs on Functional Balance in Older Subjects - Youssef, Enas Fawzy; Abd elhameed Shanb, Alsayed (The Malaysian journal of medical sciences, 2016)
Aging is associated with a progressive decline in physical capabilities and a disturbance of both postural control and daily living activities. The aim of this study was to evaluate the effects of supervised versus home exercise programs on muscle strength, balance and functional activities in older participants. Forty older participants were equally assigned to a supervised exercise program (group-I) or a home exercise program (group-II). Each participant performed the exercise program for 35-45 minutes, two times per week for four months. Balance indices and isometric muscle strength were measured with the Biodex Balance System and Hand-Held Dynamometer. Functional activities were evaluated by the Berg Balance Scale (BBS) and the timed get-up-and-go test (TUG). The mean values of the Biodex balance indices and the BBS improved significantly after both the supervised and home exercise programs ( < 0.05). However, the mean values of the TUG and muscle strength at the ankle, knee and hip improved significantly only after the supervised program. A comparison between the supervised and home exercise programs revealed there were only significant differences in the BBS, TUG and muscle strength. Both the supervised and home exercise training programs significantly increased balance performance. The supervised program was superior to the home program in restoring functional activities and isometric muscle strength in older participants.